Pop Art in Europa. - Van de Schoor, Frank; Van den Bussche, Willy; Melissen, Antoon; Wouters, Lieke (Zwolle : WBOOKS, 2012)
Alvermann, Hans Peter ; Van Amen, Woody ; Apple, Billy ; Arman ; Arroyo, Eduardo ; Asselbergs, Gustave; Axell, Evelyne ; Van Bentum, Rik ; Blake, Peter ; Boshier, Derek ; Boty, Pauline ; Broodthaers, Marcel ; Castro, Lourdes ; Christo ; Deschamps, Gérard ; Elias, Etienne ; Equipo Cronica ; Erro ; Fahlström, Öyvind ; Ferdi ; Francken, Ruth ; Freijmuth, Alphons ; Gili, Claude ; Hains, Raymond ; Hamilton, Richard ; Haworth, Jann ; Henderikse, Jan ; Hockney, David ; Van Hoeydonck, Paul ; Jacquet, Alain ; Jones, Allen ; Lindner, Richard ; Lucassen ; Mara, Pol ; Natalini, Adolfo ; Palolo, Antonio ; Panamarenko ; Paolozzi, Eduardo ; Philips, Peter ; Polke, Sigmar ; Raveel, Roger ; Raysse, Martial ; Richter, Gerard ; Rotella, Mimmo ; de Saint Phalle, Niki ; Salkin, Emile ; Schippers, Wim T. ; Spoerri, Daniel ; Stolk, Swip ; Swale, Suzan ; Tajiri, Shinkichi ; Tilson, Joe ; Tinguely, Jean ; Vostell, Wolf ; Zekveld, Jacob
Tentoonstelling 'Pop Art in Europa', Museum Het Valkhof, Nijmegen, 08.09.2012 - 06.01.2013.
Nederlands
Engels
boek